Opportunities for cooperation in removing prohibitive trade barriers - David R. DeRemer (Hungarian Academy of Sciences, Institute of Economics, 2015)
Much potential for trade liberalization exists in industries and markets with trade barriers that are prohibitive for all or many firms. In standard political economic theories of trade policy, observed prohibitive barriers must be globally optimal according to static government preferences, leaving no possibility for a trade agreement. This paper shows that for prohibitive policies in imperfectly competitive markets, a trade agreement can still play a role even without any changes in governments' policy preferences. Theory can then further identify market characteristics for which liberalization is most likely to be feasible. To illustrate the simplest case, we consider a two-country model with firms engaged in Cournot competition in segmented markets. For plausible ranges of political weights on firm profits, there is a role for a trade agreement in eliminating prohibitive trade barriers. We then consider how the potential for cooperation varies with trade costs and competition. Industries with more firm heterogeneity have greater potential for cooperation, provided that the lower productivity firms are sufficiently competitive. The implications of these results are discussed for negotiations involving either developing country exporters or services trade, two areas in which prohibitive trade barriers remain important.
Keywords: F12; F13; F15; 330; trade agreements; Cournot competition; political economy of trade policy